Bile Duct Injury During Cholecystectomy: Necessity to Learn How to Do and Interpret Intraoperative Cholangiography - Christou, Niki; Roux-David, Alexia; Naumann, David N.; Bouvier, Stephane; Rivaille, Thibaud; Derbal, Sophiane; Taibi, Abdelkader; Fabre, Anne; Fredon, Fabien; Durand-Fontanier, Sylvaine; Valleix, Denis; Mathonnet, Muriel (Frontiers in Medicine, 2021)
Introduction: Biliary duct injuries (BDI) constitute daunting complications during cholecystectomies. Per operative cholangiography (POC) has recently been generating interest in order to prevent them. However, the current literature with randomized controlled trials (RCTs) cannot conclude if POC was protective or not against the risk of BDI. Thus, the aim of our study is to analyze if POC is able to show earlier BDI and which criteria are needed to reach that point. Methods: We performed a retrospective study between 2005 and 2018 in our French reference centre, on all patients having presented a BDI during cholecystectomy and managed for that issue. Results: 22 patients were included. Nine patients had POC whereas 13 didn’t. When executed, POC was interpreted as normal (3 patients out of 9) and abnormal in 6 cases. In this latter group, only 2 cases had a BDI diagnosed intraoperatively. In other cases, the interpretation was not adequate. Conclusion: Despite their rareness, BDIs lead to deteriorating patients’ prognosis and quality of life. This study demonstrated the surgeon's responsibility to learn how to do POC properly and to read it in order to best adapt his/her behaviour to BDIs avoiding a catastrophic vicious circle of consequences.